2010
DOI: 10.1519/jsc.0b013e3181b22ab2
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Lipid Peroxidation and Antioxidant Capacity During Walking and Running of the Same and Different Intensities

Abstract: The aim was to investigate the changes in lipid peroxidation, antioxidant enzyme activities, and muscle damage in the same and different exercise intensities during walking and running. Fourteen healthy males participated in this study. The subjects' individual preferred walk-to-run transition speeds (WRTS) were determined. Each subject covered a 1.5-mile distance for 4 exercise tests; walking (WRTS-W) and running (WRTS-R) tests at WRTS, 2 kmxh-1 slower walking than WRTS (WRTS-2) and 2 kmxh-1 faster running th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Similarly, serum TBARS concentrations were significantly low in trained individuals who had high anaerobic threshold in a study (Falone et al, 2010), whereas in another research, training had no significant impact on resting MDA levels but acute exercise significantly increased the MDA levels even after the training period (Ookawara et al, 2003). In a number of studies, it has been shown that lipid peroxidation increased in untrained individuals doing acute exercise in unusual intensity (Allesio et al, 1997;Balci et al, 2010;Branth et al, 2009;Bailey et al, 2001). In a study conducted in sedentaries, sedentary group had an increased lipid peroxidation (MDA) level in their liver and skeleton muscle after acute exercise while no increment was seen in training group (Allesio and Goldfarb, 1988).…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, serum TBARS concentrations were significantly low in trained individuals who had high anaerobic threshold in a study (Falone et al, 2010), whereas in another research, training had no significant impact on resting MDA levels but acute exercise significantly increased the MDA levels even after the training period (Ookawara et al, 2003). In a number of studies, it has been shown that lipid peroxidation increased in untrained individuals doing acute exercise in unusual intensity (Allesio et al, 1997;Balci et al, 2010;Branth et al, 2009;Bailey et al, 2001). In a study conducted in sedentaries, sedentary group had an increased lipid peroxidation (MDA) level in their liver and skeleton muscle after acute exercise while no increment was seen in training group (Allesio and Goldfarb, 1988).…”
Section: Discussionmentioning
confidence: 95%
“…This agrees with the findings made by Miyazaki et al, 2001 20 in which they stated that a single bout of exercise increased blood level of MDA. Other studies by Balci et al, 2010 21 and Branth et al, 2009 22 also showed that MDA increased in untrained individuals doing acute exercise in unusual (high) intensity and the rise in serum MDA levels is dependent on exercise intensity.…”
Section: Discussionmentioning
confidence: 85%
“…The research by Balci et al [33] demonstrated that lipid peroxidation is greater when walking at a speed corresponding to the walk-to-run transition in comparison to running performed at the same speed, accompanied by higher levels of physiological stress responses (oxygen uptake, carbon dioxide output, heart rate) and energy expenditure during walking. At the same time, both efforts resulted in an increase of catalase activity in the blood of men.…”
Section: Discussionmentioning
confidence: 99%
“…In order to avoid changes in the level of physiological and biochemical response resulting from changes in the form of movement at a constant speed of locomotion [33], we assumed the form of a run for all the tests. During the first 30 minutes of the exercise, the run was performed at level, while for the last 15 minutes of the exercise, the slope angle of the treadmill was changed (only during the run at level speed remain steady).…”
Section: Submaximal Exercisesmentioning
confidence: 99%